A first exploratory comparison of the behaviour of wolves (Canis lupus) and wolf-dog hybrids in captivity - Federica Amici; Simone Meacci; Emmeline Caray; Linda Oña; Katja Liebal; Paolo Ciucci (Animal Cognition)
Abstract Extensive introgression of genes from domesticated taxa may be a serious threat for the genomic integrity and adaptability of wild populations. Grey wolves (Canis lupus) are especially vulnerable to this phenomenon, but there are no studies yet assessing the potential behavioural effects of dog-introgression in wolves. In this study, we conducted a first systematic comparison of admixed (N = 11) and non-admixed (N = 14) wolves in captivity, focusing on their reaction to unfamiliar humans and novel objects, and the cohesiveness of their social groups. When exposed to unfamiliar humans in the experimental task, wolves were more vigilant, fearful and aggressive than admixed wolves, and less likely to approach humans, but also more likely to spend time in human proximity. When exposed to novel objects, wolves were more aggressive than admixed wolves, less likely to spend time in object proximity, and more likely to interact with objects, but also less vigilant and as fearful as admixed wolves. Finally, social networks were more cohesive in wolves than in admixed wolves. Although caution is needed when comparing groups of captive individuals with different life experiences, our study suggests that dog admixture may lead to important behavioural changes in wolves, with possible implications for conservation strategies.